Teorías y modelos de cuidados de enfermería en pacientes pediátricos con leucemia. revisión bibliográfica - Chávez Coronado, Dayenara Catherine (2024)
Pediatric cancer is one of the main causes of death globally from birth to adolescence. An epidemiological analysis of childhood cancer shows that around 30% of cases are acute leukemia, and between 75% and 80% of these correspond to acute lymphoblastic leukemia (ALL); defined as a hematological disease caused by uncontrolled proliferation of immature cells or blasts. This study aims to Identify the theories and models of nursing care in pediatric patients with leukemia through a literature review to find a relationship between them and the differences. The methods used included a qualitative methodology that included a comprehensive descriptive literature review. It focused on the selection of several scientific articles supported by MESH/DEHS terms. The results highlight that the approach to these patients should not be solely pharmacological to control the symptoms, but rather suggest the need for a comprehensive approach. In addition to the use of specific drugs, other measures that improve patients' functionality, autonomy, and quality of life are utilized. In conclusion, Nursing establishes models and theories that are adaptable to different care groups, which will be directed according to the age cycles.